(untitled) (Journal of Dhaka Medical College, 2017)
Background and rationale: Antibiotic resistance is a global problem. Many factors are complexly related to the issue in multiple dimensions. Bangladesh is right in the middle of this great calamity, and is seeing the rise in resistant strains of several bacteria. Very sadly, the prevalent malpractice of abusing antibiotics in Bangladesh contributes to add complexity to the danger which may prove to be possibly the greatest threat humans have ever faced. There is much scarcity of medical literature in Bangladesh, on the antibiotic sensitivity pattern and prevalent microorganisms. Moreover, antibiotic sensitivity pattern changes over time and place. Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. This study attempts to see the prevalent microorganisms and the antibiotic sensitivity pattern in multiple types of specimens collected from Dhaka Medical College Hospital. This study also attempts to establish a way of presentation of the relevant findings which can be used in future to ensure easy comparability and contrasting of findings. Methods: The specimens were collected from the adult patients (age >12 years) admitted in the Internal Medicine ward of Dhaka Medical College Hospital, Dhaka, over a period of 6 months. The sampling technique was consecutive sampling method. Specimens which were culture positive, were only included in the study for analysis. Multiple specimens were taken. Results: S. aureus was 100% sensitive to amikacin, moxifloxacin, imipenem, meropenem, piperacillin+tazobactum combination, vancomycin, doxycycline, tetracycline, tigecycline, nitrofurantoin, azactum, linezolid and 100% resistant to cefixime. Enterobacter was 100% sensitive to penicillin, amikacin, gentamicin, netilmicin, doxycycline, tetracycline, tigecycline and 100% resistant to cefixime, ceftazidime, ceftriaxone, cefepime, cotrimoxazole, levofloxacin, vancomycin. E. coli was 100% sensitive to imipenem, meropenem, vancomycin, tigecycline and 100% resistant to mecillinam, aztreonam. Klebsiella was 100% sensitive to flucloxacillin, colistin, vancomycin, tigecycline, linezolid and 100% resistant to nalidixic acid. Proteus was 100% sensitive to cephradine, cefoxitin, cefixime, ceftazidime, ceftriaxone, cefepime, cotrimoxazole, amikacin, ciprofloxacin, imipenem, meropenem, netilmicin, piperacillin+tazobactum combination, tetracycline, tigecycline, azithromycin, azactum and 100% resistant to doxycycline, tetracycline, chloramphenicol and cefuroxime. Pseudomonas was 100% sensitive only to amikacin, netilmicin, and 100% resistant to cefixime, ceftazidime, ceftriaxone, cefepime, cotrimoxazole, gentamicin, ciprofloxacin, levofloxacin, imipenem, meropenem, doxycline, tetracycline, chloramphenicol. Salmonella typhi was 100% sensitive to amoxicillin, cefoxitin, cefixime, ceftriaxone, cefepime, cotrimoxazole, amikacin, netilmicin, azithromycin, chloramphenicol, azactum and 100% resistant to cephradine, doxycycline, tetracycline, nalidixic acid. MRSA was 100% sensitive to imipenem, vancomycin, teicoplanin, nitrofurantoin, linezolid and 100% resistant to cefpirome, cefoxitin, ceftazidime, cotrimoxazole, clindamycin, gentamicin, ciprofloxacin, netilmicin, tetracycline, clarithromycin. Acinetobacter was 100% sensitive to penicillin, cefuroxime, colistin, piperacillin+tazobactum combination, tigecycline, chloramphenicol and 100% resistant to cefixime, nalidixic acid. Citrobacter freundii was 100% sensitive to ceftazidime, ceftriaxone, cotrimoxazole, amikacin, gentamicin, ciprofloxacin, levofloxacin, imipenem, meropenem, netilmicin, nalidixic acid and 100% resistant to ampicillin, cefixime, nitrofurantoin. Conclusion: More and more antibiotics are becoming ineffective due to emergence of resistance. Serious actions should be taken. Awareness should be raised from the policy maker level to the physicians and patients. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 52-64